2021
DOI: 10.35891/tp.v12i1.2431
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan sumber nitrogen organik dalam pembuatan nata de coco

Abstract: Nata de coco is made from raw coconut water which is fermented using the Acetobacter xylinum bacteria. This product has the characteristics of a white color, a thickness of approximately 1-2 cm and a chewy texture like a gel. The largest content in nata de coco is fiber known as bacterial cellulose. In addition to requiring sugar as a carbon source, making nata de coco also requires a source of nitrogen to activate the extracellular enzymes of the Acetobacter xylinum bacteria in the manufacture of nata cellulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Researchers are looking for an alternative source of Nitrogren as a substitute for inorganic nitrogen in the production of nata de coco. The results of the study [14] showed that organic nitrogen such as tofu liquid waste, mung bean sprouts and Azolla microphylla could be an alternative to inorganic nitrogen sources (urea, ZA) which are commonly used in the production of nata de coco. These materials can be ascertained to be more environmentally friendly because they are organic material, do not cause harmful residues are easy to make and have been proven to produce high quality nata de coco [5].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers are looking for an alternative source of Nitrogren as a substitute for inorganic nitrogen in the production of nata de coco. The results of the study [14] showed that organic nitrogen such as tofu liquid waste, mung bean sprouts and Azolla microphylla could be an alternative to inorganic nitrogen sources (urea, ZA) which are commonly used in the production of nata de coco. These materials can be ascertained to be more environmentally friendly because they are organic material, do not cause harmful residues are easy to make and have been proven to produce high quality nata de coco [5].…”
Section: Introductionmentioning
confidence: 99%